CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS OF ACUTE BACTERIAL MENINGITIS IN ADULTS OF KHMELNYTSKYI REGION - Pypa, L.V.; Svistilnik, R.V.; Romanchuk, K.Yu.; Gordiichuk О.О.; Smolko, D.G. (World of Medicine and Biology, 2020)
We analyzed 123 cases of аcute bacterial meningitis, where 74 cases were in men and 49 cases - in women. 93.5% of cases began with fever, headache (86.2%), vomiting (69.9%), epileptic seizures (1.6%), altered level of consciousness (17.8%) and meningeal syndrome (80,2%). The etiological factor was established in 20.3% of patients. In 41.4% of patients neurological complications were observed. The terminal end was observed in 7.3% of patients. The main causative agent of аcute bacterial meningitis was S. pneumoniae (56.0%), the second place was taken by N. meningitidis (36.0%), the third one was divided between S. aureus and L. monocytogenes (4.0%). Brain edema (90.2%), paresis of extremities (11.7%) and epileptic seizures (7.8%) were frequent complications. The prevalence of аcute bacterial meningitis was 0.86 per 100 thousand population per year in the ratio between men and women of 1.5:1 and the total annual mortality of 0.06 per 100 thousand population.